The creation of man and woman : interpretations of the biblical narratives in Jewish and Christian traditions - Luttikhuizen, Gerard P. (Leiden Brill, 2000)
This volume deals with the three stories about the creation of man and woman in the Hebrew Bible (Genesis 1:26-27; 2:7; and 2:18-25) and with diverse interpretations of these narratives in Judaism and Christianity, particularly in ancient Jewish and Christian texts: Old Testament Apocrypha and Pseudepigrapha, Philo, the apostle Paul, Patristic, Rabbinic, and Gnostic texts. Other chapters are devoted to John Milton's recreation of Eve and Adam, to a psycho-analytical reconsideration of the biblical creation stories, and to divine creation as a model for human creation in theatre and other art forms. (Brill)
"Two of far nobler shape"
Keywords: Adam -- (Biblical figure); Eve -- (Biblical figure); Bible. -- Criticism, interpretation, etc. -- History; Creation -- History of doctrines; 222.2 -- Genesis; 233.12 -- Primitieve staat van de mens: onschuld; toestand van de zuivere natuur